The 'biomineralization toolkit' and the origin of animal skeletons. (23rd May 2020) - Murdock, Duncan J. E.
ABSTRACT: Biomineralized skeletons are widespread in animals, and their origins can be traced to the latest Ediacaran or early Cambrian fossil record, in virtually all animal groups. The origin of animal skeletons is inextricably linked with the diversification of animal body plans and the dramatic changes in ecology and geosphere–biosphere interactions across the Ediacaran–Cambrian transition. This apparent independent acquisition of skeletons across diverse animal clades has been proposed to have been driven by co‐option of a conserved ancestral genetic toolkit in different lineages at the same time. This 'biomineralization toolkit' hypothesis makes predictions of the early evolution of the skeleton, predictions tested herein through a critical review of the evidence from both the fossil record and development of skeletons in extant organisms. Furthermore, the distribution of skeletons is here plotted against a time‐calibrated animal phylogeny, and the nature of the deep ancestors of biomineralizing animals interpolated using ancestral state reconstruction. All these lines of evidence point towards multiple instances of the evolution of biomineralization through the co‐option of an inherited organic skeleton and genetic toolkit followed by the stepwise acquisition of more complex skeletal tissues under tighter biological control. This not only supports the 'biomineralization toolkit' hypothesis but also provides a model for describing the evolution of complex biological systems across the Ediacaran–Cambrian transition.